2023
DOI: 10.3390/microorganisms11071629
|View full text |Cite
|
Sign up to set email alerts
|

The Mystery of Piezophiles: Understudied Microorganisms from the Deep, Dark Subsurface

Abstract: Microorganisms that can withstand high pressure within an environment are termed piezophiles. These organisms are considered extremophiles and inhabit the deep marine or terrestrial subsurface. Because these microorganisms are not easily accessed and require expensive sampling methods and laboratory instruments, advancements in this field have been limited compared to other extremophiles. This review summarizes the current knowledge on piezophiles, notably the cellular and physiological adaptations that such m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Organisms have been found that can function down to -25 °C (psychrophiles) and up to 122 °C (hyperthermophiles) 3 . Microbial activity has been demonstrated at GPa pressures 4 , and growth at 100 MPa can has also been demonstrated (piezophiles) 5 , 6 , as well as over a wide range of pH values (acidophiles and alkaliphiles) 7 , ionic strengths (halophiles) 8 , and other stressors and even combinations thereof 9 . These living systems must modulate their protein properties to function best in their preferred environment.…”
Section: Introductionmentioning
confidence: 99%
“…Organisms have been found that can function down to -25 °C (psychrophiles) and up to 122 °C (hyperthermophiles) 3 . Microbial activity has been demonstrated at GPa pressures 4 , and growth at 100 MPa can has also been demonstrated (piezophiles) 5 , 6 , as well as over a wide range of pH values (acidophiles and alkaliphiles) 7 , ionic strengths (halophiles) 8 , and other stressors and even combinations thereof 9 . These living systems must modulate their protein properties to function best in their preferred environment.…”
Section: Introductionmentioning
confidence: 99%